The Factors Influencing Parents’ Decisions When Choosing Primary Schools for Their Children in Qatar - Alashwal, Hana Abdulmagied; Al-Kubaisi, Huda Salem; ALoqayli, Eman Abdullah; Alhadhri, Mashael Mohammed; Almarri, Noora Taleb (Dirasat: Educational Sciences, 2025)
Objectives: This study examined the extent to which financial factors, educational quality, and social factors influence parents’ decisions when selecting schools for their children. It also analyzed differences among parents based on their social and economic characteristics. Methods: A descriptive mixed-methods approach (quantitative and qualitative) was adopted. Quantitative data were collected through a questionnaire administered to a sample of 276 parents in Qatar, while qualitative data were gathered through interviews with a subsample of 32 parents to gain deeper insight into motivations and criteria behind school choice. Quantitative data were analyzed using means, standard deviations, and inferential tests (ANOVA and t-test), while qualitative data were analyzed using thematic content analysis. Results: Findings revealed that educational quality was the most influential factor in parents’ school selection decisions, followed by social factors and then financial considerations. Statistically significant differences were found in parents’ preferences based on education level, household income, and number of children enrolled, but no significant differences were found by occupation. The qualitative interviews highlighted that parents prefer schools offering high-quality education while respecting cultural values, with some expressing willingness to bear higher costs for better outcomes. Conclusions: School choice is influenced by a combination of educational, social, and financial factors, with educational quality being the top priority. The study recommends improving the quality of education in public schools, expanding education vouchers to cover a wider range of schools, and reinforcing cultural identity within the school environment.